The nurse in the management of materials in teaching hospitals - Priscila Conde Bogo; Elizabeth Bernardino; Valéria Castilho; Elaine Drehmer de Almeida Cruz (SciELO, 2015)
OBJECTIVETo present the nurse's integration within materials management of six teaching hospitals of Paraná - Brazil, and to describe the activities performed by nurses within this process.METHODA study of a qualitative approach and descriptive nature, conducted in teaching hospitals in Paraná, between June and August of 2013. The data collection was conducted through semi-structured interviews with eight nurses who worked in materials management; data were analyzed using content analysis.RESULTSThese showed that nurses perform ten categories of activities, distributed into four of the five steps of the materials management process.CONCLUSIONThe nurse, in performing of these activities, in addition to favoring the development of participative management, contributes to the organization, planning, and the standardization of the hospital supply process, giving greater credibility to the work with professionals who use the materials, and to the suppliers.